Secure Microprocessor-Controlled Prosthetic Leg for Elderly Amputees: Preliminary Results - S. Krut; Ch. Azevedo Coste; P. Chabloz (Applied Bionics and Biomechanics)
We introduce a new prosthetic leg design, adapted to elderly trans-femoral amputees. Technical progress in prosthesis design mainly concerns active individuals. An important number of elderly amputees are not very mobile, tire easily, present reduced muscle strength, and have difficulties managing their balance. Therefore, the needs and characteristics of this specific population are very different from those of younger ones and the prosthetic solutions are not adapted. Our artificial knee has been designed to fulfill the specific requirements of this population in terms of capabilities, transfer assistance, security, intuitiveness, simplicity of use, and types of physical activity to be performed. We particularly focused our efforts on ensuring safe and secure stand-to-sit transfers. We developed an approach to control the different states of the prosthetic joint (blocked, free, resistant), associated with different physical activities. Amputee posture and motion are observed through a single multi-axis force sensor embedded in the prosthesis. The patient behaves naturally, while the controller analyses his movements in order to detect his intention to sit down. The detection algorithm is based on a reference pattern, calibrated individually, to which the sensor data are compared, and submitted to a set of tests allowing the discrimination of the intention to sit down from other activities. Preliminary validation of the system has been performed in order to verify the applicability of the prosthesis to different tasks: walking, standing, sitting down, standing up, picking up an object from a chair, slope and stair climbing.